Existential feminism in Rintik Sedu’s short stories: Female subjectivity, freedom, and the search for authentic selfhood - Santi Dwi Kusuma; Nafa Adelia Satya Pradani; Annisa Ramadhani Wachid; Zahra Amanda Putri; Mutiara Ayu Cahyaningtyas; Krisandra Pangestika; Laela Febiani; Onok Yayang Pamungkas (Journal of Language, Literature, Social and Cultural Studies, 2026)
This study aims to analyze the representation of existentialist feminism Simone de Beauvoir in a collection of digital short stories by Rintik Sedu published through the Rintiksedu.com website. This research uses a qualitative paradigm with a hermeneutic approach to interpret the meaning of literary texts. The source of the research data is six digital short stories by Rintik Sedu, namely No Answer is the Answer, Our Parts, Dialogue at that time, Limits, Between Us Pt.1&2, and I Write This Because I Am Afraid of Forgetting. The research data is in the form of words, sentences, and discourses that represent the existence of women and efforts to achieve existential freedom. The results of the study show that the existence of women in these short stories is represented through three categories: existence based on nature that describes the social construction of women's patience and sacrifice; existence based on history that shows the awareness of female figures to break the inheritance of previous generations' habits; and existence based on myths that question romantic and patriarchal stereotypes in interpersonal relationships. Women's efforts to achieve authentic existence are manifested through two strategies: rejecting the position of the "other" by affirming agency and personal freedom, and strategically accepting social expectations to gain space to move within patriarchal structures. This study concludes that digital literary works can serve as an important medium in representing women's struggle to achieve existential freedom and dismantling the social constructs that limit their authentic existence.